EB experiment. Laboratory post-mortem analyses report - Villar, M.Victoria; Campos, Ramón; Gutiérrez-Nebot, Luis (My University, 2014)
The EB experiment was run by ENRESA at the Mont Terri Underground Research Laboratory in Switzerland, starting in October 2000, with the aim of demonstrating that automated production of a Granular Bentonite Material (GBM) and its emplacement in the upper part of a clay barrier were feasible (ENRESA 2005). The lower part of the barrier was composed by blocks of compacted bentonite on which the dummy canister rested. This report summarises the physical and thermo-hydro-mechanical characterisation performed at CIEMAT laboratories of bentonite samples taken during the EB experiment dismantling.
Deliverable del proyecto UE PEBS
Keywords: bentonite barrier; nuclear waste disposal; bentonite pellets; saturation